Matrix Metalloproteinase Inhibitor MMI-166 Suppresses the Growth of SW1990 Human Pancreatic Cancer Cells - Wu, Junben; Shahbaz, Muhammad; Wang, Shujing; Gong, Bengang; Liang, Benjia; Fang, Ruliang; Qiu, Bo; Jiang, Min; Li, Yang; Niu, Jun (Current Signal Transduction Therapy, 2014)
Objectives: As a selective matrix metalloproteinase inhibitor, MMI-166 specifically inhibits MMP-2 and MMP-9 activity and represses tumor invasion and metastasis. Previous studies show that MMI-166 has an anti-metastatic role in a variety of tumors. However, it still remains unclear about the exact effect of MMI-166 on human pancreatic cancer. Methods: In this study, we showed firstly MMI-166 induced proliferation inhibition and apoptosis of SW1990 human pancreatic cancer cells in both dose- and time-dependent manners in vitro. We successfully established a human pancreatic cancer xenograft model in nude mice and verified the inhibition effect of MMI-166 on MMP-2 and MMP-9. Results: More importantly, by using this model, we further demonstrated MMI-166 suppressed growth of SW1990 pancreatic cells xenograft in vivo by inducing cells apoptosis. In addition, we examined the expression of a series of apoptosis-related proteins and found MMI-166 inhibited the expression of c-Myc. Conclusion: Our work demonstrates that MMI-166 may be of therapeutic value in the treatment of pancreatic cancer.
Keywords: Animal experimentation